Optimalisasi Layanan Perpustakaan Dalam Meningkatkan Minat Baca Siswa - Moch Basit Aulawi (IAIN Ponorogo, 2011)
The key to use a knowledge treasury on library,especiallyschool library, is reading. And the process of reading a literature willbe maximal if it is done by interest in reading. In addition to havingmain duty, such as information, circulation and reference service,school library has a role to increase interest in reading of students.A lot of services of library to increase student’s interest in readingare thosewhich become part of learning process, services to increasestudent’s skill to explore information, and services to increasealibrary use. So, the library has many opportunites to increasestudent’s interest in reading. The main point in increasing student’sinterest in reading is a model from many parts, especially librarian.Those process will form a paradigm thereading is the main matterinlearning process.This essay will explore library’s role to increasestudent’s interest in reading.